Making Futures Marginal Notes on Innovation, Design, and Democracy - Ehn, Pelle; Nilsson, Elisabet M.; Topgaard, Richard (The MIT Press, 2014)
Experiments in innovation, design, and democracy that search not for a killer app but for a collaboratively created sustainable future.Innovation and design need not be about the search for a killer app. Innovation and design can start in people's everyday activities. They can encompass local services, cultural production, arenas for public discourse, or technological platforms. The approach is participatory, collaborative, and engaging, with users and consumers acting as producers and creators. It is concerned less with making new things than with making a socially sustainable future. This book describes experiments in innovation, design, and democracy, undertaken largely by grassroots organizations, non-governmental organizations, and multi-ethnic working-class neighborhoods.These stories challenge the dominant perception of what constitutes successful innovations. They recount efforts at social innovation, opening the production process, challenging the creative class, and expanding the public sphere. The wide range of cases considered include a collective of immigrant women who perform collaborative services, the development of an open-hardware movement, grassroots journalism, and hip-hop performances on city buses. They point to the possibility of democratized innovation that goes beyond solo entrepreneurship and crowdsourcing in the service of corporations to include multiple futures imagined and made locally by often-marginalized publics. ContributorsMåns Adler, Erling Björgvinsson, Karin Book, David Cuartielles, Pelle Ehn, Anders Emilson, Per-Anders Hillgren, Mads Hobye, Michael Krona, Per Linde, Kristina Lindström, Sanna Marttila, Elisabet M. Nilsson, Anna Seravalli, Pernilla Severson, Åsa Ståhl, Lucy Suchman, Richard Topgaard, Laura Watts